2017
DOI: 10.1371/journal.pone.0188329
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity analysis of distracted drivers based on the wavelet phase coherence of functional near-infrared spectroscopy signals

Abstract: The present study aimed to evaluate the functional connectivity (FC) in relevant cortex areas during simulated driving with distraction based on functional near-infrared spectroscopy (fNIRS) method. Twelve subjects were recruited to perform three types of driving tasks, namely, straight driving, straight driving with secondary auditory task, and straight driving with secondary visual vigilance task, on a driving simulator. The wavelet amplitude (WA) and wavelet phase coherence (WPCO) of the fNIRS signals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 82 publications
1
50
0
Order By: Relevance
“…The pre-processing method for fNIRS data, which has been described in detail in previous studies (Han et al, 2014 ; Xu et al, 2017 ), was conducted as follows. First, moving average method was applied to remove the noise-like abrupt spikes caused by movement artifacts or background light.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-processing method for fNIRS data, which has been described in detail in previous studies (Han et al, 2014 ; Xu et al, 2017 ), was conducted as follows. First, moving average method was applied to remove the noise-like abrupt spikes caused by movement artifacts or background light.…”
Section: Methodsmentioning
confidence: 99%
“…First, the moving average method was applied to remove the noise-like abrupt spikes caused by the movement artifacts or background light, involving an algorithm based on moving standard and spine interpolation routines[ 47 , 48 ]. After the removal of abnormal points, the delta [HbO 2 ] and MAP signals were band-pass filtered with a Butterworth filter at a low cut-off frequency of 0.005 Hz to remove extremely slow variations and a high cutoff frequency of 2 Hz to remove the uncorrelated noise components.…”
Section: Methodsmentioning
confidence: 99%
“…Although the origin of LFOs remains controversial in the literature, studies have found that the endothelial, neurogenic, and myogenic controls are the main mechanisms responsible for maintaining CBF constant during blood pressure fluctuations [22]. Previous studies have classified LFOs into four frequency intervals: I (0.005-0.0095 Hz), II (0.0095-0.02 Hz), III (0.02-0.07 Hz) and IV (0.07-0.2 Hz) [23][24][25][26][27][28][29]. Interval-I and interval-II reflect respectively nitric oxide (NO) dependent and independent endothelial metabolic activities [24,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have classified LFOs into four frequency intervals: I (0.005-0.0095 Hz), II (0.0095-0.02 Hz), III (0.02-0.07 Hz) and IV (0.07-0.2 Hz) [23][24][25][26][27][28][29]. Interval-I and interval-II reflect respectively nitric oxide (NO) dependent and independent endothelial metabolic activities [24,26,27]. Interval-III and interval-IV correspond, respectively, to neurogenic and myogenic related metabolic activities [23,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation